ANALYSIS OF THE EXTENSION OF A BUSINESS IN THE FIELD OF PUBLIC FOOD - Daniela SIMTION (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Assessing the performance and financial position of a company calculated on the basis of the information provided by the companies in the financial statements reveals a certain trend of the company. The defining objective of financial management is to increase the firm's market value. The decisive factor that contributes to the increase of the value of the company are the investments. Investments give the company’s identity. Thus, the first and decisive step towards increasing the market value of the firm is to make good investment decisions. This paper focuses on analysing and evaluating the expansion project of AMIOGO restaurant. Indicator values: Net current value, Internal Return Rate or Investment Recovery Duration indicate the viability and attractiveness of the proposed project. At the same time the possibility that the analyzed company can develop is highlighted or not: at what terms, during what time period, in what value limits, with what risks.